Air Quality - Measurement and Modeling 2016
DOI: 10.5772/64919
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Monitoring: A Case Study from Romania

Abstract: The first section of this chapter provides an up-to-date general view of air pollution/air quality topic. It indicates main pollutants and their sources and impacts and presents and discusses current air quality standards and air quality indexes worldwide; how datasets are acquired, gathered and analyzed and how the measurements are then interpreted are also presented. Recent works containing updated and detailed technical discussions for each issue addressed and additional web resources are mentioned. The gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our results for PM 10 fit within those in reference [7]. Figure 2 and Figure 3 illustrate the average seasonal variation of cadmium and PM 10 mass concentrations for Iasi (for the years when the highest levels were registered) and, respectively Cluj.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Our results for PM 10 fit within those in reference [7]. Figure 2 and Figure 3 illustrate the average seasonal variation of cadmium and PM 10 mass concentrations for Iasi (for the years when the highest levels were registered) and, respectively Cluj.…”
Section: Resultssupporting
confidence: 71%
“…High levels of PM 10 mass concentrations in Iasi and Cluj were first revealed in reference [7] where the annual and seasonal temporal trends of PM 10 and PM 2.5 for Iasi and Cluj, together with other urban and rural sampling sites in Romania were also reported. Our results for PM 10 fit within those in reference [7].…”
Section: Resultsmentioning
confidence: 99%
“…While the AQI is normally used to report the daily air quality at each monitoring station, in this study it was used to assess the monthly variability and to underline the multi-annual trends using all four operational stations in Cluj-Napoca city, considering that a single monitoring station is not representative for a city and did not reflect spatial variations of PM 10 . Therefore, the daily AQI was calculated based on the average PM 10 concentration obtained for the operational stations and the EU daily limit value (50 µg/m 3 ) [45,46]. The daily AQI was further aggregated to obtain the monthly AQI.…”
Section: Air Quality Indexmentioning
confidence: 99%
“…From table 3, ATV and mean CO concentrations across three periods of sampling at the six sampling points falls within the limit (10,000-20,000 μgm-3 ) set standard (NESREA, 2009) [37] , and the results reported by another researcher and the team (Ezeh et al, 2012) [19] . The CO variation across the periods at all sampling points also revealed that the air quality contained less than 10,000 μgm-3 minimum standard stipulated by WHO (WHO, 2000) [55] and reported by Iorga (2016) [25] . The highest level of CO was recorded at SP1 with mean value of up to 8690.00 μgm -3 .…”
Section: Average Traffic Volume and Average Estimate Of Co Emission C...mentioning
confidence: 87%